An Analysis of Extrovert and Introvert Personality of the Students on Speaking Performance at the Tenth Grade of State Islamic Senior High School 1 Padang Lawas - Hasibuan, Mufhidatul husna; Roza, Melinda; Chanti Dianan Seri (English Education, Linguistics, and Literature Journal, 2023)
Abstract: This research aims to analyze students' speaking performances based on the extrovert and introverted personalities of students in the tenth grade of State Islamic Senior High School 1 Padang Lawas. This research uses a descriptive-qualitative method with a case study approach. The data were collected by Eysenck Personality Questionnaires (EPQ), speaking tests, and interviews. After the data was collected, it was analyzed using the Miles and Huberman model technique, which consists of three stages of data analysis: data reduction, data presentation, and verification or conclusion. The population in this study were students of class X-science, consisting of 198 students from a total of five classes. The sample used in this study amounted to 20 students using the proportional technique in the take of the sample. The findings showed that each of the 20 research samples—ten extroverts and ten introverts—had different speaking performance scores. The results of the speaking test from ten extrovert students obtained five students with good criteria and five with poor criteria. Meanwhile, the results of the speaking test for ten introverted students found that five students with poor criteria, four students obtained good criteria and one student received a speaking test result with very good criteria. From each of the extrovert and introvert students who were interviewed, they stated that they experienced several obstacles: a lack of preparation before performing, a lack of knowledge about language aspects, mispronunciation, and a lack of vocabulary. It can be concluded that students with various personality types can use various learning methods that suit the needs of each student. Therefore, whether an extrovert or an introvert, speaking performance will be better if students have sufficient linguistic knowledge and are also supported by frequent participation or good preparation.